Endothelial Cell-Specific Molecule-1 Inhibits Albuminuria in Diabetic Mice. Issue 12 (29th December 2022) - Zheng, Xiaoyi; Higdon, Lauren; Gaudet, Alexandre; Shah, Manav; Balistieri, Angela; Li, Catherine; Nadai, Patricia; Palaniappan, Latha; Yang, Xiaoping; Santo, Briana; Ginley, Brandon; Wang, Xiaoxin X.; et al.
Key Points: Circulating endothelial cell-specific molecule-1 (Esm-1) inversely correlates with diabetic kidney disease. Addition of Esm-1 in susceptible mice reduces albuminuria, and deletion of Esm-1 in resistant mice mildly worsens albuminuria. Esm-1 attenuates podocyte injury and select IFN signaling, highlighting innate immunity as a potential mechanism of kidney disease. Visual Abstract: Abstract : Background: Diabetic kidney disease (DKD) is the most common cause of kidney failure in the world, and novel predictive biomarkers and molecular mechanisms of disease are needed. Endothelial cell-specific molecule-1 (Esm-1) is a secreted proteoglycan that attenuates inflammation. We previously identified that a glomerular deficiency of Esm-1 associates with more pronounced albuminuria and glomerular inflammation in DKD-susceptible relative to DKD-resistant mice, but its contribution to DKD remains unexplored. Methods: Using hydrodynamic tail-vein injection, we overexpress Esm-1 in DKD-susceptible DBA/2 mice and delete Esm-1 in DKD-resistant C57BL/6 mice to study the contribution of Esm-1 to DKD. We analyze clinical indices of DKD, leukocyte infiltration, podocytopenia, and extracellular matrix production. We also study transcriptomic changes to assess potential mechanisms of Esm-1 in glomeruli. Results: In DKD-susceptible mice, Esm-1 inversely correlates with albuminuria and glomerular leukocyte infiltration. We show that overexpression of Esm-1 reduces albuminuria and diabetes-induced podocyte injury, independent of changes in leukocyte infiltration. Using a complementary approach, we find that constitutive deletion of Esm-1 in DKD-resistant mice modestly increases the degree of diabetes-induced albuminuria versus wild-type controls. By glomerular RNAseq, we identify that Esm-1 attenuates expression of kidney disease–promoting and interferon (IFN)-related genes, including Ackr2 and Cxcl11 . Conclusions: We demonstrate that, in DKD-susceptible mice, Esm-1 protects against diabetes-induced albuminuria and podocytopathy, possibly through select IFN signaling. Companion studies in patients with diabetes suggest a role of Esm-1 in human DKD.